2017
DOI: 10.5194/amt-2016-423
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of nocturnal Aerosol Optical Depth from lunar photometry at Izaña high mountain Observatory

Abstract: Abstract. This work is a first approach to correct the systematic errors observed in the aerosol optical depth (AOD) retrieved at night-time using lunar photometry and calibration techniques dependent on the lunar irradiance model. To this end, nocturnal AOD measurements were performed in 2014 using the CE318-T master Sun-sky-lunar photometer (Lunar-Langley calibrated) at Izaña high mountain Observatory. This information has been restricted to 59 nights characterized as clean and stable according to lidar vert… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Here we make use of one implementation of the ROLO named as RIMO (ROLO Implementation for Moon's Observation; Barreto et al, 2019). The irradiance from these models is usually assumed as true for the AOD calculation, however different authors reported some uncertainties and biases in these models (e.g., Viticchie et al 2013;Lacherade et al 2014;Barreto et al 2017;Geogdzhayev and Marshak 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Here we make use of one implementation of the ROLO named as RIMO (ROLO Implementation for Moon's Observation; Barreto et al, 2019). The irradiance from these models is usually assumed as true for the AOD calculation, however different authors reported some uncertainties and biases in these models (e.g., Viticchie et al 2013;Lacherade et al 2014;Barreto et al 2017;Geogdzhayev and Marshak 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As it has been shown in previous works (Barreto et al, 2017(Barreto et al, , 2019 it is important to assume that night-time AOD uncertainty is larger that the uncertainty of daytime retrievals, and that it will also depend on Moon phase angle. These facts also pose additional difficulty to the cloud screening, apart from the lack of the aureole radiance check to detect thin clouds.…”
Section: Night-time Aod Evaluationmentioning
confidence: 97%
“…However, in Moon photometry this cycle, as equation (3.10) evidences, could be also caused by inaccuracies in the used E M 0 values. Barreto et al (2017) found a similar behaviour in these differences but being close to zero for MPA≈0 and increasing with the absolute phase, which could be explained because they used Lunar Langley calibration near to the full Moon and it masked the possible bias on RIMO at least close to MPA≈0. Assuming the Gain calibration and AOD ref are accurate, and all the differences between AOD and the reference are caused by RIMO inaccuracies, the ∆AOD G−r can be expressed as 1 :…”
Section: Resultsmentioning
confidence: 58%
“…However, the possible errors and uncertainties in E M 0 are propagated to the value of κ obtained by this method, although these uncertainties are partially masked in the AOD retrieval (equation (3.10)) because the E M 0 values are also used in the calculation. Recently, Barreto et al (2017) found a dependence on MPA and MZA of the AOD calculated by this Lunar Langley method.…”
Section: Gain Calibration Methodsmentioning
confidence: 93%
See 1 more Smart Citation